Aortic Stiffness and White Matter Microstructural Integrity Assessed by Diffusion Tensor Imaging: The ARIC‐NCS. Issue 6 (17th March 2020) - Wei, Jingkai; Palta, Priya; Meyer, Michelle L.; Kucharska‐Newton, Anna; Pence, Brian W.; Aiello, Allison E.; Power, Melinda C.; Walker, Keenan A.; Sharrett, A. Richey; Tanaka, Hirofumi; Jack, Clifford R.; Mosley, Thomas H.; et al.
Abstract : Background: Changes in white matter microstructural integrity are detectable before appearance of white matter lesions on magnetic resonance imaging as a manifestation of cerebral small‐vessel disease. The information relating poor white matter microstructural integrity to aortic stiffness, a hallmark of aging, is limited. We aimed to examine the association between aortic stiffness and white matter microstructural integrity among older adults. Methods and Results: We conducted a cross‐sectional study to examine the association between aortic stiffness and white matter microstructural integrity among 1484 men and women (mean age, 76 years) at the 2011 to 2013 examination of the ARIC‐NCS (Atherosclerosis Risk in Communities Neurocognitive Study). Aortic stiffness was measured as carotid‐femoral pulse wave velocity. Cerebral white matter microstructural integrity was measured as fractional anisotropy and mean diffusivity using diffusion tensor imaging. Multivariable linear regression was used to examine the associations of carotid‐femoral pulse wave velocity with fractional anisotropy and mean diffusivity of the overall cerebrum and at regions of interest. Each 1‐m/s higher carotid‐femoral pulse wave velocity was associated with lower overall fractional anisotropy (β=−0.03; 95% CI, −0.05 to −0.02) and higher overall mean diffusivity (β=0.03; 95% CI, 0.02–0.04). High carotid‐femoral pulse wave velocity (upper 25th percentile) was associated with lower fractional anisotropy (β=−0.40; 95% CI, −0.61 to −0.20) and higher overall mean diffusivity (β=0.27; 95% CI, 0.10–0.43). Similar associations were observed at individual regions of interest. Conclusions: High aortic stiffness is associated with low cerebral white matter microstructural integrity among older adults. Aortic stiffness may serve as a target for the prevention of poor cerebral white matter microstructural integrity.